Brilho etéreo de arquivos e lembranças: Algumas questões sobre arquivos pessoais e biografias - De Silva, Wilton Carlos Lima [UNESP] (Universidade Estadual de Maringa, 2017)
The modest goal of the paper is to present, in a brief and panoramic way, some thoughts on the challenges of biographical research through personal files. To do so, from some examples seeks to draw attention to the need of the young researcher to realize the file and its documentary resources as technical and socio-historical construction, questioning the stored document functionality and, in particular, some nuances of personal files regarding the reconstruction of an individual trajectory.
Ethereal glow of files and memories: Some questions about the personal papers and biographies
Keywords: Autobiography; Biography; Memory; Personal papers; Supplies